2007
DOI: 10.1242/jcs.001370
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cellular cholesterol on membrane-cytoskeleton adhesion

Abstract: Whereas recent studies suggest that cholesterol plays important role in the regulation of membrane proteins, its effect on the interaction of the cell membrane with the underlying cytoskeleton is not well understood. Here, we investigated this by measuring the forces needed to extract nanotubes (tethers) from the plasma membrane, using atomic force microscopy. The magnitude of these forces provided a direct measure of cell stiffness, cell membrane effective surface viscosity and association with the underlying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
162
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 172 publications
(178 citation statements)
references
References 72 publications
16
162
0
Order By: Relevance
“…This observation was highly unexpected because previous studies showed that in membrane lipid bilayers an increase in membrane cholesterol increases the stiffness of the membrane 5,17 . Our further studies confirmed these observations using several independent approaches, including Atomic Force Microscopy 18,19 and Force Traction Microscopy …”
supporting
confidence: 80%
See 1 more Smart Citation
“…This observation was highly unexpected because previous studies showed that in membrane lipid bilayers an increase in membrane cholesterol increases the stiffness of the membrane 5,17 . Our further studies confirmed these observations using several independent approaches, including Atomic Force Microscopy 18,19 and Force Traction Microscopy …”
supporting
confidence: 80%
“…In contrast, optical tweezesrs are used to pull membrane nanotubes (tethers) to estimate cortical tension and membrane-cytoskeleton adhesion 37 . An alternative method to pull membrane tethers is to use the AFM, a method that has both significant similarities and differences as compared to optical tweezers 18,38 . The advantage of most of these methods is that they may provide detailed spatial information about the biomechanical properties of the individual cells.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, although the abundance and organization of the sphingolipid domains were influenced by cholesterol, nonrandom sphingolipid clustering was more drastically affected by cytoskeleton disruption than by cholesterol depletion. In fact, the altered sphingolipid organization observed after mβCD treatment was likely caused by cholesterol depletion-induced changes in cytoskeleton organization (31)(32)(33)35) and not by a loss of cohesive cholesterol-sphingolipid interactions. Because the cholesterol-sphingolipid interactions seem to play a minor role in sphingolipid domain formation, we conclude that the sphingolipid domains are not lipid rafts and are instead a distinctly different sphingolipid-enriched plasma membrane domain.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, cytoskeletal assembly and disassembly appears to be closely associated with changes of membrane shape [34,35]. CHOL presumably plays a role in such shape changes, as the degree of cytoskeleton-membrane adhesion in plasma membranes was reported to depend on CHOL concentration in the membrane [36]. CHOL was also observed to be critically involved in the reversible wrinkling and folding of the membrane during the normal breathing cycle in the lung.…”
Section: Resultsmentioning
confidence: 99%